Effect of SO2 and steam on CO2 capture performance of biomass-templated calcium aluminate pellets - Erans Moreno, Maria; Beisheim, T.; Manovic, Vasilije; Jeremias, M.; Patchigolla, Kumar; Dieter, H.; Duan, Lunbo; Anthony, Edward J. (Royal Society of Chemistry, 2016)
Four types of synthetic sorbents were developed for high-temperature post-combustion calcium looping CO2 capture using Longcal limestone. Pellets were prepared with: lime and cement (LC); lime and flour (LF); lime, cement and flour (LCF); and lime, cement and flour, doped with seawater (LCFSW). Flour was used as a templating material. All samples underwent 20 cycles in a TGA under two different calcination conditions. Moreover, the prepared sorbents were tested for 10 carbonation/calcination cycles in a 68-mm-internal-diameter bubbling fluidized bed (BFB) under three environments: with no sulphur and no steam; in the presence of sulfur; and with steam. When compared to limestone, all the synthetic sorbents exhibited enhanced CO2 capture performance in both a TGA and BFB, with the exception of the sample doped with seawater. In the BFB tests, the addition of cement binder during the pelletisation process resulted in the increase of CO2 capture capacity from 0.08 gCO2/gsorbent (LF) to 0.15 gCO2/gsorbent (LCF) by the 10th cycle. The CO2 uptake in the presence of SO2 dramatically declined by the 10th cycle; for example, from 0.22 gCO2/gsorbent to 0.05 gCO2/gsorbent in the case of the untemplated material (LC). However, as expected all samples showed improved performance in the presence of steam and the decay of reactivity during the cycles was less pronounced. Nevertheless, in the BFB environment, the templated pellets showed poorer CO2 capture performance. This is presumably because of material loss due to attrition under the FB conditions. Namely, by contrast, the templated materials performed better than untemplated materials under TGA conditions. This indicates that reduction in attrition is critical in the case of employment of templated materials in realistic systems with FB reactors.